ANALISIS STARTING MOTOR INDUKSI PADA BALL MILL PLANT DENGAN LIQUID RESISTANCE STARTER DI PT CITRA PALU MINERALS - Alfito, Muhammad Bintang; Adam, Ahmad Antares; Martdiansyah, Martdiansyah; Mukhlis, Baso; Pirade, Yulius Salu; Masarrang, Maryantho (Foristek, 2025)
The 3700 kW induction motor at the Ball Mill Plant at PT Citra Palu Minerals requires an effective starting method to prevent current surges and voltage drops during initial operation. This study aims to analyze the starting performance of induction motors using three starting methods, namely Liquid Resistance Starter (LRS), Direct On Line (DOL), and Wye-Delta. The analysis is carried out by mathematical calculations through the induction motor equivalent circuit to obtain the starting current, starting torque, starting power and starting voltage values of each starting method. The calculation results show that the LRS method produces a starting current of 421.47 A, a starting torque of 42,259.84 Nm, a starting power of 4,423.19 kW and a starting voltage of 6,374.40 V. Compared to DOL and Wye Delta, the LRS method provides better performance in terms of limiting current and maintaining voltage stability, and is able to produce higher torque and power. The calculation of the LRS method also shows conformity with the actual data in the field, so that the model used can be used as a technical reference. Based on the analysis results, the LRS method is considered the most suitable for starting high power induction motors in heavy-load applications such as Ball Mill Plant.